JUMPA Vol.3 No.1 Feb 2016 ANALISIS LOADING FAKTOR SUMBER DAYA MANUSIA DAN PENGARUHNYA TERHADAP NILAI ORGANISASI: ANALISIS LOADING FAKTOR SUMBER DAYA MANUSIA DAN PENGARUHNYA TERHADAP NILAI ORGANISASI - Enggal Sriwardiningsih Binus University (Jurnal Manajemen dan Perbankan (JUMPA), 2016)
This study examined the factor analysis Empowerment of Human Resources and Organizational Values ​​influence on a company. The object of this study is the Company XYT as research objects. Model theory of empowerment (Empowerment) involves several factors: Desire, Trust, Confident, Credibility, Accountability and Communication which is then managed by three perspectives, namely: the perspective of performance management, training and development perspective (training and development). Empowerment is right will contribute to the optimization of the performance of organizations and companies. The approach used in this study is kuatintatif approach using regression methods. Data collection techniques used in this study using the Library Research yaitudengan way of studying books, reference, and journals relevant to the problems studied and Field Research using questionnaires and direct interviews with respondents. Results of the study revealed that the empowerment model have positive relationships and influences that factor is a factor confindent Human Resources Empowerment most dominant organizational values ​​while Credibility factor is the factor of Human Resource Empowerment less dominant on the value of the organization.